A seat at the table : persons with disabilities and policy making - Boyce, William (McGill-Queen's University Press, 2001)
A Seat at the Table documents the participation of disability activists and organizations in public policy making in Canada. The authors combine studies of contemporary federal and provincial policy making with a historical perspective on the progress made by disability groups since World War I. The cases they discuss illustrate the tension between issues of human rights and personal capacities that the disability movement must deal with, but which have implications for other groups as well. An analysis of contemporary social policy networks in Canada makes it possible for the authors to suggest reasons for the inconsistent success that disability organizations have had in translating their requirements into policy. A Seat at the Table illuminates the key social-political factors of resources, roles, and reputations that must be taken into account by excluded groups seeking to gain a seat at the policy table. The insights it provides are important for the development of more professional lobbying practices by disability stakeholders as well as by women, aboriginals, ethnic groups, the elderly, and the poor.